#1**0 **

I assume you mean \(\sqrt{p+a+r}=k\).

Whenever there is a square root symbol, you want to square the equation.

\((\sqrt{p+a+r})^2=k^2\)

This becomes \(p+a+r=k^2\), because the square root symbol is lifted.

Now we can add and subtract values on each side of the equation to find a. I think you can do that.

You are very welcome!

:P

CoolStuffYT Nov 1, 2019

#1**0 **

Best Answer

I assume you mean \(\sqrt{p+a+r}=k\).

Whenever there is a square root symbol, you want to square the equation.

\((\sqrt{p+a+r})^2=k^2\)

This becomes \(p+a+r=k^2\), because the square root symbol is lifted.

Now we can add and subtract values on each side of the equation to find a. I think you can do that.

You are very welcome!

:P

CoolStuffYT Nov 1, 2019